Characterizing the Epidemiology of Postoperative Transfusion-related Acute Lung Injury. (January 2015) - Clifford, Leanne; Jia, Qing; Subramanian, Arun; Yadav, Hemang; Wilson, Gregory A.; Murphy, Sean P.; Pathak, Jyotishman; Schroeder, Darrell R.; Kor, Daryl J.
<x xml:space="preserve">Abstract</x> Background: Transfusion-related acute lung injury (TRALI) is the leading cause of transfusion-related death in the United States; however, it remains poorly characterized in surgical populations. To better inform perioperative transfusion practice, and to help mitigate perioperative TRALI, the authors aimed to better define its epidemiology before and after TRALI mitigation strategies were introduced. Methods: This retrospective cohort study examined outcomes of adult patients undergoing noncardiac surgery with general anesthesia who received intraoperative transfusions during 2004 (n = 1, 817) and 2011 (n = 1, 562). The demographics and clinical characteristics of transfusion recipients, blood transfusion descriptors, and combined TRALI/possible TRALI incidence rates were evaluated. Univariate analyses were used to compare associations between patient characteristics, transfusion details, and TRALI mitigation strategies with TRALI/possible TRALI incidence rates in a before-and-after study design. Results: The incidence of TRALI/possible TRALI was 1.3% (23 of 1, 613) in 2004 versus 1.4% (22 of 1, 562) in 2011 (P = 0.72), with comparable overall rates in males versus females (1.4% [23 of 1, 613] vs. 1.2% [22 of 1, 766]) (P = 0.65). Overall, thoracic (3.0% [4 of 133]), vascular (2.7% [10 of 375]), and transplant surgeries (2.2% [4 of 178]) carried the highest rates of TRALI/possible TRALI. Obstetric and gynecologic surgical patients had no TRALI episodes. TRALI/possible TRALI incidence increased with larger volumes of blood product transfused (P < 0.001). Conclusions: Perioperative TRALI/possible TRALI is more common than previously reported and its risk increases with greater volumes of blood component therapies. No significant reduction in the combined incidence of TRALI/possible TRALI occurred between 2004 and 2011, despite the introduction of TRALI mitigation strategies. Future efforts to identify specific risk factors for TRALI/possible TRALI in surgical populations may reduce the burden of this life-threatening complication.